An Analysis of Cybersecurity Policies and Practices in Public Administration - Arief, Aulia Ramdhani (Journal of Public Representative and Society Provision, 2022)
In this research, the purpose is to assess the major strong and weak points of cybersecurity policies and strategies in the chosen public administration organisation. The type of research used is the qualitative case study and as such, focuses on interviews and policy documents in line with cybersecurity laws and related reports from the selected experts. There is used themes that are grounded in the data to look at patterns that recurred regularly. As a conclusion it can be stated that the situation in an organization is quite good as it has a clear security policy, controls and regular training for its employees, but there are some issues with an access control, vulnerability assessment and penetration testing. The advancement in these areas will assist the organisation to safeguard data and avoid cyber attacks in future and make sure the organization understands that cybersecurity is not a definite state and the organisational bureaucracy has to embrace change in practices continually due to the dynamic threat.